Associations between professional identity and turnover intent in prehospital emergency physicians: The mediating effect of burnout - Xingmiao Feng; Yu Wang; Pengyu Jia; Yadong Wang; Zhongjun Guan; Zhongjun Guan; Kai Meng (Frontiers Media S.A., 2022)
ContextThe prehospital emergency system is essential for reducing mortality and disability in emergency patients. However, the high turnover rate of prehospital emergency physicians (PEPs) remains the most prominent problems in the prehospital emergency system. Turnover intent (TI) is predictive of actual turnover behavior; however, previous studies have mainly focused on sociodemographic factors and job characteristics, ignoring many other potential psychological factors, such as professional identity (PI) and job burnout (JB).ObjectivesTo measure the level of PI, JB, and TI of PEPs in Beijing, China. We analyze the distribution of TI in different social demography PEPs and then further explore the influence of PI and JB on TI, to provide a reference and suggestions for government departments to reduce the TI of PEPs.MethodsAn online questionnaire was distributed to 552 PEPs in Beijing, and a total of 533 valid questionnaires were included. T-test and variance analysis were used to examine the differences in the distribution of TI among different sociodemographic PEPs. Pearson's correlation analysis was used to test the correlation between PI, JB, and TI. The SEM was used to analyze the relationships among PI, JB, and TI.ResultsUnivariate analysis showed that age, marital status, education, professional title, work experience, department and hukou were significantly associated with TI. Pearson's correlation analysis showed that PI was negatively associated with JB and TI, and JB was positively associated with TI. Professional treatment identity (PTI, β = −0.24, 95% CI: −0.38~-0.11), professional meaning identity (PMI, β = −0.12, 95% CI: −0.23~0.03), and emotional exhaustion (EE, β = 0.40, 95% CI: 0.28~0.51) seem to have direct impacts on TI. Given the mediating role played by EE, PTI may have an indirect negative effect on TI (β = −0.24, 95% CI: −0.32~0.16).ConclusionPI and JB of PEPs in China are closely related to TI, which may have unexpected effects on government departments to stabilize the team of PEPs through a series of control measures. According to the above results, the professional treatment of PEPs needs to be improved, and external learning opportunities should be increased. Legalization of medical rescue workers should also be on the agenda.